Management of Patients With Chemotherapy-Induced Nausea and Vomiting - Barbour, Sally Yowell (J Adv Pract Oncol, 2017)
Despite advances in the management of chemotherapy-induced nausea and vomiting (CINV), clinical management remains a challenge and CINV continues to be a side effect that patients fear most. Advanced practitioners can play a major role in evidence-based interventions for prevention and management of these side effects of treatment.